Determination of domoic acid in shellfish extracted by molecularly imprinted polymers. Issue 16 (12th July 2016) - Lin, Zhengzhong; Wang, Dan; Peng, Aihong; Huang, Zhiyong; Lin, Yuhui
Abstract : A selective sample cleanup method using molecularly imprinted polymers was developed for the separation of domoic acid (a shellfish toxin) from shellfish samples. The molecularly imprinted polymers for domoic acid was prepared by emulsion polymerization using 1, 3, 5‐pentanetricarboxylic acid as the template molecule, 4‐vinyl pyridine as the functional monomer, ethylene glycol dimethacrylate as the crosslinker, and Span80/Tween‐80 (1:1 v/v) as the composite emulsifiers. The molecularly imprinted polymer showed high affinity to domoic acid with a dissociation constant of 13.5 μg/mL and apparent maximum adsorption capacity of 1249 μg/g. They were used as a selective sorbent for the detection of domoic acid from seafood samples coupled with high‐performance liquid chromatography. The detection limit of 0.17 μg/g was lower than the maximum level permitted by several authorities. The mean recoveries of domoic acid from clam samples were 93.0–98.7%. It was demonstrated that the proposed method could be applied to the determination of domoic acid from shellfish samples.